PENGARUH CAPITAL ADEQUACY RATIO, LOAN TO DEPOSIT RATIO, NON-PERFORMING LOAN, BEBAN OPERASIONAL PENDAPATAN OPERASIONAL DAN NET INTEREST MARGIN TERHADAP PROFITABILITAS - Nathania Rebecca Yakub; Murtanto Murtanto (EBID: Ekonomi Bisnis Digital, 2024)
Research has the intention of testing the influence of capital adequacy ratio, loan to deposit ratio, non-performing loans, operating expense operating revenue and net interest margin on the profitability of banking companies. This research collects data using financial reports and annual reports from 2021 to 2023 on banking companies listed on the Indonesia Stock Exchange. The number of samples used in the research was 34 banking companies. Descriptive statistical analysis and multiple regression analysis are used as analysis methods. The results show that capital adequacy ratio and net interest margin have a significant positive influence on profitability, while non-performing loans and operating expenses operating revenue have a significant negative influence on profitability. Loan to deposit ratio does not have a significant influence on profitability. Simultaneously, all independent variables have an effect on the dependent variable.